BALI DIPROYEKSIKAN MENGALAMI BONUS DEMOGRAFI PUNCAK 2020-2030 Peluang atau bencana? - Rimbawan, Nyoman Dayuh (PIRAMIDA; Vol 10 No 1 (2014): Jurnal PIRAMIDA, 2014)
Bali is one of the 33 provinces in Indonesia. It is a relatively narrow is 5636.66 km2 (0.29 percent of the total area of Indonesia). With a population of nearly 3.9 million people (SP 2010), this means the population density reaches 690 inhabitants / km2 (large ranks seventh after the provinces in Java). Bali experienced a demographic dividend peak earlier and longer duration than the national. Therefore, the Balinese economy potentially developed earlier and longer than the national level. Bali is projected to experience a demographic bonus peak period 2020-2030. This period Bali dependency ratio is lowest at 42.2 to 43.3 percent between. Favorable demographic bonus is not automatic. According Aswatini (2012), benefits can be learned if there is readiness of government policies such as strengthening investment in health, education and employment. But to be a disaster if the productive population in conditions of low education, low skills, and poor health conditions, which makes it able to produce optimally. However, the requirement to take advantage of the demographic bonus as the engine of economic growth unlikely to be performed optimally. This is due to the quality of its human resources is still relatively low. Human investment as long term while the demographic bonus has been in front of the eye. On the other hand the investment made by the government through its budget is relatively low because most of the funds allocated for routine costs as a consequence of bureaucratic fat. Instead of private investment opportunities are not many because Bali poor in natural resources. Limited investment opportunities resulting in productive age population is abundant because of the demographic bonus peaks can not be used optimally.
Keywords: demographic bonus, investment in human resources, economic growth